Massage Therapy, Mapping Of Mother's Knowledge And Their Effect On Baby Weight - Musdalina Musdalina; Alfi Laili; Ruri Aditya Sari (Science Midwifery, 2021)
The government's target in reducing the prevalence of stunting aims to reduce the number of people who are not qualified, because it will have an impact on the country's economy. Phase 1 data collection method was carried out by distributing questionnaires to 40 mothers who gave birth in Langkat, Deli Serdang and Medan. In the second stage, data collection was carried out using a quasi-experimental design. The approach taken is a non-randomized pre and post test with control design. Respondents in the second stage were 20 infants aged 6-12 months.Based on massage therapy performed by mothers for very large babies, as many as 21 people (52.5%). Data analysis using Chi-Squared p value = 0.019 < (0.05), meaning that there is a significant relationship between mother's knowledge and massage therapy for babies. In the first month of massage, the baby's average weight increased by 49 grams, then there was an increase in the baby's weight again in the second month, namely an increase of 40 grams and in the 3rd month an increase in body weight of 94 grams. Weight gain in infants from 0 months - 3 months, then it can be seen that the weight gain in babies who are given massage is above the weight of babies who are not given massage.